2007
DOI: 10.1073/pnas.0703383104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of growth 4 (ING4) is up-regulated by a low K intake and suppresses renal outer medullary K channels (ROMK) by MAPK stimulation

Abstract: Dietary K intake plays an important role in the regulation of renal K secretion: a high K intake stimulates whereas low K intake suppresses renal K secretion. Our previous studies demonstrated that the Src family protein-tyrosine kinase and mitogen-activated protein kinase (MAPK) are involved in mediating the effect of low K intake on renal K channels and K secretion. However, the molecular mechanism by which low K intake stimulates MAPK is not completely understood. Here we show that inhibitor of growth 4 (IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This research group suggests that MAPK-induced inhibition of ROMK activity plays a predominant role in suppressing K + secretion in the early stage (<24 h) of K + depletion. Further study supports the hypothesis that ING4 (inhibitor of growth 4), which is stimulated by low K + intake dependent on superoxide anion production, may mediate the effect of a low-K + diet on MAPK to depress ROMK channel activity (67). In summary, a low-K + diet increases superoxide anion production, which, in parallel, increases the expression and activity of ( a ) PTK and ( b ) ING4 and MAPK, which in turn independently depress CCD K + channel activity and K + secretion (67).…”
Section: Molecular Mechanisms Of Renal K+ Adaptationsupporting
confidence: 68%
“…This research group suggests that MAPK-induced inhibition of ROMK activity plays a predominant role in suppressing K + secretion in the early stage (<24 h) of K + depletion. Further study supports the hypothesis that ING4 (inhibitor of growth 4), which is stimulated by low K + intake dependent on superoxide anion production, may mediate the effect of a low-K + diet on MAPK to depress ROMK channel activity (67). In summary, a low-K + diet increases superoxide anion production, which, in parallel, increases the expression and activity of ( a ) PTK and ( b ) ING4 and MAPK, which in turn independently depress CCD K + channel activity and K + secretion (67).…”
Section: Molecular Mechanisms Of Renal K+ Adaptationsupporting
confidence: 68%
“…The present study has further suggested that PP2B may also be involved in mediating the effect of superoxide anions on ERK and p38 phosphorylation: 1) treatment of M-1 cells or 293T cells with GO decreased the expression of PP2B-cat, and 2) inhibition of PP2B significantly stimulated the phosphorylation of p38 and ERK. The idea that the effect of K restriction on PP2B-cat is mediated by superoxide anions is also supported by the observation that K restriction did not decrease the level of PP2B-cat in gp91 phox (Ϫ/Ϫ) mice, which have been shown to produce less superoxide anion in the kidney than WT mice (46). However, further experiments are required to explore the relationship between PP2B and ING4 in mediating the effect of low K intake or superoxide anions on MAPK.…”
Section: Discussionsupporting
confidence: 50%
“…A previous study provided evidence supporting the idea that the tumor-suppressing protein inhibitor of growth 4 (ING4) is involved in mediating the effect of superoxide on MAPK in the kidney (46). First, low K intake increased ING4 expression, and suppression of superoxide abolished the effect of K restriction on ING4 expression.…”
Section: Discussionmentioning
confidence: 73%
“…One of the key functions of the kidney is maintaining plasma K homeostasis [167]. In renal K secretion regulation, low K intake increases ING4 expression in a superoxide-dependent manner, subsequently stimulating mitogen-activated protein kinase (MAPK) to depress renal outer medullary potassium (ROMK) channel activity [168]. Furthermore, ING4 was found to play an active role in the multi-system autoimmune disease.…”
Section: Impact On Human Disorders Other Than Cancermentioning
confidence: 99%